Cardiac concentric hypertrophy promoted by activated Met receptor is mitigated in vivo by inhibition of Erk1, 2 signalling with Pimasertib. (April 2016) - Sala, Valentina; Gallo, Simona; Gatti, Stefano; Medico, Enzo; Vigna, Elisa; Cantarella, Daniela; Fontani, Lara; Natale, Massimo; Cimino, James; Morello, Mara; Comoglio, Paolo Maria; Ponzetto, Antonio; et al.
Abstract: Cardiac hypertrophy is a major risk factor for heart failure. Hence, its attenuation represents an important clinical goal. Erk1, 2 signalling is pivotal in the cardiac response to stress, suggesting that its inhibition may be a good strategy to revert heart hypertrophy. In this work, we unveiled the events associated with cardiac hypertrophy by means of a transgenic model expressing activated Met receptor. c-Met proto-oncogene encodes for the tyrosine kinase receptor of Hepatocyte growth factor and is a strong inducer of Ras-Raf-Mek-Erk1, 2 pathway. We showed that three weeks after the induction of activated Met, the heart presents a remarkable concentric hypertrophy, with no signs of congestive failure and preserved contractility. Cardiac enlargement is accompanied by upregulation of growth-regulating transcription factors, natriuretic peptides, cytoskeletal proteins, and Extracellular Matrix remodelling factors (Timp1 and Pai1). At a later stage, cardiac hypertrophic remodelling results into heart failure with preserved systolic function. Prevention trial by suppressing activated Met showed that cardiac hypertrophy is reversible, and progression to heart failure is prevented. Notably, treatment with Pimasertib, Mek1 inhibitor, attenuates cardiac hypertrophy and remodelling. Our results suggest that modulation of Erk1.2 signalling may constitute a new therapeutic approach for treating cardiac hypertrophies. Graphical abstract: Highlights: Activated Met in the heart induces concentric cardiac hypertrophy. Cardiac growth is accompanied by increased cytoskeletal protein levels. The hypertrophic response elicits remodelling of ECM but not fibrosis. Suppression of activated Met reverses hypertrophy and prevents heart failure. Cardiac hypertrophy is reduced by pharmacological mitigation of Erk1, 2 signalling.